Manfaat Buah Kurma - Praptiwi, Praptiwi; Arti, Dwi Windu Kinanti (Universitas Muhammadiyah Semarang, 2017)
Benefits of DatesBackground: Sweetener is always related to its cariogenecity. White sugar is the most cariogenic sweetener, while date rich of natural sucrose and fructose. Date tannin and magnesium have anti infection and anti inflammation properties. The analytical laboratoric study using experimental design wanted to know the differencies between saliva pH after consumptions of sucrose, fructose, and date. The study was executed in Faculty of Dentistry and Integrated Laboratory of Muhammadiyah University in Semarang, 2016.Methods: Sample of study was 18 students of the Faculty having caries ≤ 2. Initial pH saliva was measured after ½ hour fasting, followed by tap water rinsing, consumptions of 1 g sucrose, 1 g fructose, and a date. Result: T dependent test, and one way Anova were used. Mean of saliva pH and SD were found consecutively as follows, initial 6.92; 0.217; tap water rinsing 6.91; 0.151, sucrose consumption 6.83; 0.229, fructose 6.90; 0.156, and date 7.04; 0.086. No significant difference between initial pH and after tap water rinsing. There was significant difference between saliva pH after sucrose, fructose, and date consumptions (p value 0.002; p < 0.05).Conclusion: Saliva pH after consumptions of sucrose and fructosa were lower than date; sucrose and fructose were more acidic and cariogenious than date.